Neonatal Screening for Congenital Hypothyroidism: A Study Conducted in a Tertiary Care Hospital of Gujarat - Shubhangi Rathod; Ramesh Pradhan; Rosy Lekharu; Jaydip Vala; Mehak Kulshrestha (Indian Journal of Medical Biochemistry)
Background: Growth and differentiation of the fetal brain largely depend on the thyroidal biochemical cascade. The most common cause of congenital hypothyroidism (CH) is thyroid dysgenesis. Maternal iodine deficiency remains to be the predominant cause of underactive thyroid in neonates. Congenital hypothyroidism fulfils Wilson and Jungners criteria for newborn screening, in having a suitable test, and treatment and that the costs of screening, confirmation, and treatment are balanced against the overall costs of not screening. Aims and objectives: Aims: Assessment of possible methods for screening/early detection of CH in neonates. Primary objective: Compare and correlate cord blood (CB) thyroid stimulating hormone (TSH) with heel prick TSH, as a marker of CH. Materials and methods: In a prospective study approved by the Ethical Committee of GCS Medical College and Hospital, Ahmedabad, 100 neonates (50 males and 50 females) were assessed for thyroid status after excluding those born of known hypothyroid mothers or having a history of distress. Cord blood was collected at the time of delivery, and dried blood spots (DBS) from heel prick at 72 hours were collected and TSH was compared. Results: The findings were comparable in both samples as mean TSH CB = 6.14 ± 2.82 mIU/L vs mean TSH DBS = 6.21 ± 3.03 mIU/L; p-value = 0.9268 at 95% confidence interval and r-value for TSH = 0.9783. This was true in normal delivery as well as LSCS births.